Sexual abuse of young children in southern Africa - 2004. (Cape Town : HSRC Press, 2004)
This volume is the first attempt in the region to grapple with the full complexity of child sexual abuse in southern Africa. A range of experts present the facts, assess the depiction of the problem in the press, consider legal and policy responses and offer accounts of interventions in South Africa, Mozambique and Zimbabwe.
Includes bibliographical references and index.
Adult
Keywords: Antiquities